Long-term effects of web-based pedometer-mediated intervention on COPD exacerbations. (February 2020) - Wan, Emily S.; Kantorowski, Ana; Polak, Madeline; Kadri, Reema; Richardson, Caroline R.; Gagnon, David R.; Garshick, Eric; Moy, Marilyn L.
Abstract: Background: Technology-based physical activity (PA) interventions have been shown to improve daily step counts and health-related quality of life, but their effect on long-term clinical outcomes like acute exacerbations (AEs) is unknown in persons with COPD. Methods: U.S. Veterans with stable COPD were randomized (1:1) to either pedometer alone (control) or pedometer plus a website with feedback, goal-setting, disease education, and a community forum (intervention) for 3 months. AEs were assessed every 3 months over a follow-up period of approximately 15 months. Pedometer-assessed daily step counts, health-related quality-of-life (HRQL), and self-efficacy were assessed at baseline, end-of-intervention at 3 months, and during follow-up approximately 6 and 12 months after enrollment. Zero-inflated Poisson models assessed the effect of the intervention on risk for AEs, compared to controls. Generalized linear mixed-effects models for repeated measures examined between-group and within-group changes in daily step count, HRQL, and self-efficacy. Results: There were no significant differences in age, FEV1 % predicted, baseline daily step count, AEs the year prior to enrollment, or duration of follow-up between the intervention (n = 57) and control (n = 52) groups. The intervention group had a significantly reduced risk of AEs (rate ratio = 0.51, [95%CI 0.31–0.85]), compared to the control group. There were no significant between-group differences in change in average daily step count, HRQL, or self-efficacy at 6 and 12 months after enrollment. Conclusions: A 3-month internet-mediated, pedometer-based PA intervention was associated with reduced risk for AEs of COPD over 12–15 months of follow-up. ClinicalTrials.gov identifier: NCT01772082. Highlights: COPD patients exhibit reduced physical activity, often early in the course of disease. Interventions promoting physical activity improve short-term symptoms and activity. Long-term benefits of physical activity promotion are not well studied. 3-month website-plus-pedometer intervention improved short-term physical activity. Website-plus-pedometer intervention reduced acute exacerbations over 15–18 months.